Pemanfaatan Serat Bambu Apus Sebagai Bahan Pembuatan Helm Safety - Syahputra, Amri; Nayan, Ahmad; Adhiya Putra, M. Iqbal; Aljufri, A; Suryadi, S (Malikussaleh Journal of Mechanical Science and Technology, 2024)
The use of apus bamboo fiber material as an alternative material to fiber glass in the materials sector, especially in safety helmets, is now becoming increasingly well known to people. This is because the advantages of this natural fiber reinforced composite material are environmentally friendly, lighter weight, relatively cheap price, excellent mechanical properties, and easy to obtain. So the aim of this research is to determine the process of making safety helmets using the vacuum infusion method and to determine the strength of free fall test specimens reinforced by apus bamboo fiber. As a result of the vacuum infusion method, the safety helmet that is made has a smoother surface with the same thickness. The resulting helmet has a bottom length of 30 cm, width 22 cm, height 14 cm and top length 24 cm. The free fall test uses variations in height from a fall distance of 1 meter, 2 meters and 3 meters. Meanwhile, the loads are 0.694 kg and 1.563 kg. The results of the potential energy sensor for a load of 0.694 kg at a height of 1 meter is 5.59 joules, a load of 0.694 kg at a height of 2 meters is 12.39 joules, and a load of 0.694 kg at a height of 3 meters is 19.18 joules. Meanwhile, sensor data for a load of 1,563 kg at a height of 1 meter is 14.11 joules, a load of 1,563 kg at a height of 2 meters is 29.42 joules, and a load of 1,563 kg at a height of 3 meters is 44.74 joules.